Asclepiades of Bithynia's Medical Molecular Theory and his Contribution to Evolving Understandings of Mental Illness - Brady, Frank Anthony (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Asclepiades of Bithynia (124 BC-40 BC) was a Greek physician who practiced and taught Greek medicine in Rome in the late second and early first century BC. His unique medical system was strongly influenced by Epicurean philosophy. He sought to construct a new theory of human disease derived in part from the atomic theory of chance and evolution described earlier by Democritus and Epicurus. He is generally accepted by most scholars as being the first leading representative of Greek theoretical medicine to work as a practicing physician in Rome. When he first arrived in Rome his knowledge of medicine and philosophy, coupled with his considerable rhetorical skills and personality allowed him not only to flourish as a physician, but to be accepted into the intellectual and sophisticated aristocratic circles that existed in Rome during the late Republican period. Asclepiades was boldly challenging the long-standing Hippocratic doctrine of the four bodily humors, as well as its benevolent nature axiom. Asclepiades held that a fully-fledged theory of matter was necessary for the understanding and practice of medicine and was positing an innovative systematic medical theory that drew extensively on Epicurean atomism. He was saying that the human body, as well as everything else in the universe, was composed of tiny, imperceptible particles, which he called onkoi. According to his theory these seamless masses were in perpetual motion, bouncing around forever within a void space, without having any providential intelligence at work in the universe to guide them. He postulated that these onkoi were of different shapes and sizes, lacking colour and sensitivity and possessing the capacity to aggregate together by chance to form larger masses that would ultimately form all of the components of the universe, including the human body. Unlike the indivisible theoretical atoms of Epicurus, Asclepiades was saying that these onkoi were uniquely capable of splitting into innumerable smaller fragments which would move around constantly within the void space. His mechanistic theory of medicine was saying that good health is maintained by the free and balanced motion of the onkoi through these pores and channels that lay within the void space, whereas disease is primarily the consequence of the blockage or impaction of the onkoi passing through the pores that are situated at particular sites throughout the human body, with specific diseases resulting from such blockages at these different sites. This specific localization of pathological phenomena was fundamental to Asclepiades' approach to diagnosis and treatment. His approach to the management of disease, especially mental illnesses, was reasoned, humane was in so many ways ahead of its time. As a result of his many contributions and his overall approach to patient care, this somewhat neglected physician is now considered by many medical historians as being the father of molecular medicine (Yapijakis, 2009). Asclepiades' ideas about the composition of the human body and disease processes at the microscopic level anticipated later developments in the scientific field, including the modern understanding of molecular biology and medicine. This thesis explores the life and times of Asclepiades and how his unique theoretical framework for the understanding of human disease, which diverged from the dominant medical paradigms of his time, contributed to the promotion of a more humane approach to patient care, particularly in the context of mental health.
APPROVED
Keywords: Asclepiades of Bithynia; Greek medicine; History of medicine; History of psychiatry; Mental illness; Molecular medicine; Tracheostomy